The Capabilities of Amlodipine/Lisinopril Single-Pill Combination in the Treatment of Newly Diagnosed Arterial Hypertension in a Middle-Aged Patient (Case Report) - A. I. Kochetkov; M. V. Lopukhina; E. A. Kotaeva; A. A. Kirichenko; O. D. Ostroumova (Столичная издательская компания, 2020)
Arterial hypertension (AH) is one of the most significant modifiable risk factors that increase cardiovascular morbidity and mortality worldwide, including Russia. The complex of structural and functional changes in the heart that occurs during AH consists not only in the formation of left ventricular (LV) myocardial hypertrophy, but also in the myocardial stiffness increasing due to collagen formation and cardiomyocytes apoptosis. These abnormalities are substrate for diastolic function disturbances, electrical myocardial instability and ischemia. The article provides a clinical case of amlodipine/lisinopril single-pill combination (A/L SPC) use in real clinical practice in a patient with stage II grade 2 newly diagnosed AH and its effect on blood pressure and echocardiographic myocardial fibrosis markers, including speckle tracking parameters The high antihypertensive efficacy of A/L SPC, a favorable effect on blood pressure circadian rhythm, as well as pronounced target-organ protective properties, in particular the ability to reduce LV and left atrial stiffness, were demonstrated. So, we conclude that A/L SPC improve the elastic properties of the left heart.